Relational Transdisciplinarity and Artistic/Academic Knowledge Production - Fendler, Ute; Gruber, Valerie; Ndi, Gilbert Shang (Annual Conference of the Africa Multiple Cluster of Excellence "Africa*n Relations : Modalities Reflected", 2021)
Whereas the multiple entanglements between Africa and its Latin American diasporas can hardly be squeezed into the boundaries established by the academic field, transdisciplinary cooperation between academics and artists offers a fruitful way out of disciplinary bottlenecks. In this roundtable, we will share insights into modalities of relating and translating that enable and restrain transdisciplinary knowledge production. As a first result of the Participatory Action Research programme carried out at the intersection of the Cluster projects “Moral Geographies of Re-Existence” and “Black Atlantic Revisited”, we will launch a video performance created by the artists Diego Araúja (Brazil), Lobadys Pérez (Colombia) and Matchume Zango (Mozambique). Taking a cue from the transdisciplinary video, we will jointly reflect on processes, products and pitfalls of border-crossing knowledge creation. In this vein, we aim at stimulating debates on innovative modes of doing research in ways that enhance in-depth and multi-perspectival analyses. Our contribution adds to discussions on knowledge transfer and dissemination with a view to widening the audience and raising the social impact of social sciences, humanities and the arts. Ultimately, multiple relations between Africa and its diasporas require multiple modes of knowledge production, reflection and diffusion in order to overcome historical and disciplinary strictures.